How Cool Stuff Works - Woodford, Chris [et. al] (London Dorling Kindersley Ltd., 2005)
Ever wondered why your trainers are so comfy or how your mobile works? You use many kinds of incredible technology every day but do you have any idea how they really work? Flip to the facts in this book with illustrations and explanations. Dazzle your friends with your knowledge of gadgets and gizmos.
Include Color Illustrations and Index.
Keywords: Technological innovations -- Inventions -- High technology